Effect of “maccog” TCM tea on improving glucolipid metabolism and gut microbiota in patients with type 2 diabetes in community - Hu, Biyue; Yin, Tongtong; Zhang, Jiajia; Liu, Minjing; Yun, Hang; Wang, Jian; Guo, Renmei; Huang, Jie; Zhou, Yixia; Meng, Hongyan; Wang, Li (Frontiers in Endocrinology, 2023)
Objectives: This work aimed to observe the effect of consuming Chinese herb tea on glucolipid metabolism and gut microbiota in patients with type 2 diabetes mellitus (T2DM). Methods: Ninety patients with T2DM were recruited from a community and randomly divided into the control group (CG) and intervention group (IG). CG maintained conventional treatment and lifestyle, and IG accepted additional “maccog” traditional Chinese medicine (TCM) tea (mulberry leaf, radix astragali, corn stigma, cortex lycii, radix ophiopogonis, and gynostemma) for 12 weeks. Glucolipid metabolism, hepatorenal function, and gut microbiota were then measured. Results: After the intervention, the decreases in fasting plasma glucose (FPG) and total cholesterol (TC) were greater (P<0.05) in IG than in CG, and those in glycosylated serum protein (GSP) were almost significantly greater (P=0.066) in IG than in CG. The total protein (TP), albumin (ALB), and creatinine (CREA) levels in IG were significantly lower and their decreases were larger in IG than in CG (P<0.05) after the intervention. The Ace and Chao1 indices in IG were slightly higher after the intervention (P=0.056 and 0.052, respectively) than at baselines. The abundance of Actinobacteria, Lachnospiraceae, Bifidobacteriaceae, and Phascolarctobacterium increased significantly after the intervention in IG (P<0.05), and the abundance was higher in IG than in CG (P<0.05 or P＜0.1). The abundance of Clostridiales and Lactobacillales was negatively correlated with FPG (P<0.05), Clostridiales and Lachnospiraceae was negatively correlated with GSP (P<0.05), and Bacteroides/Firmicutes was positively correlated with both (P<0.05). No adverse event was observed during the intervention. Conclusions: Administration of “maccog” TCM tea for 12 weeks slightly improved glucolipid metabolism and significantly increased the abundance of beneficial gut microbiota in community patients with T2DM. The increase in beneficial bacteria abundance may be involved in the improvement of glucose metabolism indicators. In addition, this intervention is safe and feasible.